The effect of net profit margin, return on investment, and current ratio toward financial performance in health sector companies listed of Indonesia stock exchange for 2021–2024 period - Shinta Gevira Farina; Sunarmi Sunarmi (Indonesia Accounting Research Journal, 2025)
This study aims to examine and analyze the influence of Net Profit Margin, Return on Investment, and Current Ratio on the financial performance of health sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. Financial performance in this study is proxied by Return on Assets (ROA). The research population consists of 35 companies in the health sector, with a sample of 10 companies over 4 years, resulting in 40 data points. The research was conducted from April to June 2025. This study uses a quantitative approach with multiple linear regression analysis processed using SPSS version 23. The results show that Net Profit Margin, Return on Investment, and Current Ratio have a positive effect on financial performance (ROA). These findings support Signaling Theory, which explains that strong financial ratios such as high profitability and liquidity send positive signals to investors regarding the company's condition and prospects. Therefore, it is recommended to improve operational efficiency, manage investments optimally, and maintain liquidity to achieve stable and sustainable financial performance.